Analisis Zonasi Hijau di Jakarta - Retno Setiowati; Hayati Sari Hasibuan; Raldi Hendro Koestoer (Diponegoro University, 2021)
Rapid development and increasing population causes the green open space in Jakarta is decreasing in size every year. Green open space is one of the keys to the sustainability of a city. The purpose of this study was to analyze the area of green space, green space distribution, and deviation between the green zone plan of the Regional Regulation of RDTR PZ and existing green space in Jakarta using Geographic Information Systems. Based on satellite imagery in 2018, the area of green space in Jakarta is 3,473.94 ha (5.31%). The highest green space area in 2018 is in the green belt zone (H4) of 1,557.88 ha and the lowest in the urban forest zone (H1) is 235.13 ha. The green zoning plan based on the Regional Regulation on RDTR and PZ is only 7,520.96 ha (11.51%) and is far from the mandate stipulated in Law Number 26 Year 2007 and the Jakarta 2030 RTRW of 30%. The highest area of green open space in the Regional Regulation of RDTR and PZ is in the green belt zone (H4) of 4,539.40 ha and the lowest in the urban forest zone (H1) is 17,58 ha. Based on the comparison of the area of green space in 2018 with the green plan RDTR and PZ it is known that there are 4 administrative city areas that experience a shortage of green space, namely South Jakarta, East Jakarta, West Jakarta and North Jakarta, while for Central Jakarta it has exceeded the green plan specified.